Conocimiento y manejo domiciliario de enfermedad diarreíca aguda en madres atendidas en el Establecimiento de Salud Túpac Amaru Iquitos 2023 - Lizama Lopez, Estefany Priscila (2024)
The general objective of the study was to determine the relationship between knowledge about acute diarrheal disease and home management of the treatment of Acute Diarrheal Disease in mothers of children under 5 years of age treated at the CRED consulting room of the Túpac Amaru Health Establishment, Iquitos 2023. Quantitative study with a non-experimental, correlational design that had a sample of 36 mothers with children under 5 years of age. The technique was the interview and the instruments were the knowledge questionnaire about EDA (validity of 95.83% and reliability of 96.09%), and the questionnaire on home management of EDA treatment (validity of 93.5% and reliability of 94.2%). Results: in knowledge about EDA, 47.2% have poor knowledge, 33.3% have fair knowledge and 19.5% have good knowledge. In the home management of EDA treatment, 58.3% have poor home management, 27.8% have regular management and 13.9% have optimal management. Applying the Chi Square, significant results were obtained X 2 c = 42,400; df = 4; p = 0.000; α = 0.05. Conclusion: Mothers with good knowledge about acute diarrheal disease will carry out optimal home management of the treatment of acute diarrheal disease in their children under 5 years of age.